Iowa RBA, November 4, 1996 - Fuller, James L.et al; Iowa Ornithologists' Unionet al (1996)
Iowa RBA update for November 4, 1996. Highlights of the update include a Brown Pelican, a Black Scoter, a Pacific Loon, and Prairie Falcons. Other interesting observations were of a Red Phalarope, Red-necked Grebe, Gyrfalcon, and several species of Gulls. Also included are handwritten notes for the next week's update with sightings of 9 Sparrow species and a Western Grebe. Epson - sheet feed/flatbed